Design, implementation, and outcomes of an in-service program with photovoice as a pedagogical tool for geography teachers. Issue 2 (22nd April 2022) - Cho, Chul-Ki; Kim, Byung-Yeon; Stoltman, Joseph P.
Abstract: The purpose of this study was to introduce photovoice as a pedagogical tool in an in-service program for geography teachers, demonstrate the implementation of this methodology, and examine its outcomes, strengths, and weaknesses. The applicability of photovoice as a pedagogical tool for secondary school geography as well as its strengths and weaknesses were clarified. As a pedagogical tool for geography, photovoice not only allowed in-service geography teachers to develop critical thinking, but also fostered active citizenship. In addition, photovoice afforded in-service geography teachers the opportunity to capture the public geography learned in the classroom in the field and subsequently add their own voice to discover their own personal geography. Despite these strengths, in order for geography teachers to employ photovoice in their classes, issues such as time, evaluation, place, and safety as well as inviting decision-makers and policymakers to the presentation process are challenges that need to be addressed. As this study focuses on geography teacher education, further research needs to be done with younger students.